Revealing schoolchildren's key situations in the use of digital media inside and outside school: A media diary study. - Jennifer Virginie Meier; Kai Kaspar (PLoS ONE)
Introduction Digital media have become integral to schoolchildren's lives, both within educational and non-educational settings. Educators emphasize the importance of bridging the gap between school learning and children's out-of-school activities. To identify potential variations and commonalities, we investigated key situations with digital media among lower secondary schoolchildren in Germany, aiming to determine which themes are especially relevant in different settings. Methods We analyzed the media usage of German schoolchildren (ages 10 to 17) in class and outside of school using a mixed-method approach with a focus on the qualitative facets of key situations. For this purpose, 49 schoolchildren from seven schools were asked to complete media diaries. Over a six-week period, they documented key situations with details on setting, emotional experiences, post-communication, social support, and self-reflection. We analyzed the key situations using content and frequency analyses. Results The schoolchildren reported 145 key situations, from which we developed a categorization system comprising 15 distinct categories. The most reported key situations involved "playing video games", "digital learning or homework", and "online communication or content sharing". Most key situations (115) took place outside of school, while 30 occurring in class. Schoolchildren mostly reported key situations that involved feelings of happiness and low levels of arousal. They discussed key situations more often and in greater depth with family members and school friends, and less often with school staff or non-school friends. Key situations were discussed more often face-to-face than online. Notably, schoolchildren engaged in self-reflection on their key situations, including concerns about excessive media use. Discussion Overall, the study provides comprehensive insights into the digital media behaviors of schoolchildren, highlighting individual differences and preferences. The discussion offers valuable implications for both educational practice and future research, particularly regarding the integration of digital media into formal educational settings.